A modified preparation method for a wide-range mesophase asphalt-based silicon-carbon composite electrode material

By preparing a silicon-carbon composite electrode material with a "carbon-silicon-vacuum-carbon" quadratic structure, the structural powdering and instability caused by volume expansion of the silicon-based anode are solved, and electrochemical properties with high specific capacity and high magnification are achieved.

CN115513438BActive Publication Date: 2025-03-07CHINA UNIV OF PETROLEUM (EAST CHINA)
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211257399.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-14
Publication Date
2025-03-07
Estimated Expiration
2042-10-14

AI Technical Summary

Technical Problem

Volume expansion of silicon-based anode in dense silicon anode results in structural powdering and the continuous formation of unstable solid electrolyte membranes, hindering the practical application of silicon-based anode.

Method used

By strictly controlling the reaction conditions, using wide-area petroleum-based mesophase as carbon source, silicon-carbon composite materials are prepared through hydrothermal reaction and magnesium thermal reduction, and using calcium carbonate as the sacrificial layer to form a silicon-carbon composite electrode material with a quadratic structure of "carbon-silicon-vacuum-carbon".

Benefits of technology

A silicon-carbon composite electrode material with high specific capacity and high magnification is achieved, which effectively restricts the excessive expansion of silicon and improves the conductivity, rate performance and cycling performance of the electrode material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115513438B_ABST
    Figure CN115513438B_ABST
Patent Text Reader

Abstract

The invention discloses a modification preparation method of a wide-area mesophase asphalt-based silicon-carbon composite electrode material, which uses petroleum-based wide-area mesophase asphalt as a carbon source and oxygen-containing organosilicon as a silicon source. Through a hydrothermal reaction, the organosilicon is first deposited in situ on the surface of the carbon material to form a uniform coating layer, and the silicon-carbon combination is tighter; the void structure generated by calcium carbonate as a sacrificial layer reserves enough space for the expansion of silicon, and the outermost layer is coated with the wide-area mesophase asphalt again to prepare a silicon-carbon composite electrode material with a "carbon-silicon-void-carbon" quaternary structure. The petroleum-based wide-area mesophase asphalt has the characteristics of consistent arrangement and orientation of carbon layer construction units and high flatness of the carbon layer, which effectively ensures the smooth embedding and extraction of lithium ions during long-term circulation and has high cycle stability. The prepared electrode material has the advantages of good conductivity, good rate performance, and stable cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of lithium ion battery electrode materials and relates to a modification preparation method of a silicon-carbon composite electrode material. Background Art

[0002] Lithium-ion batteries (LIBs) are important energy storage devices today. They have the advantages of high energy density, high power density, and long service life. They have been widely used in portable appliances, aerospace, hybrid vehicles, and other fields. With the increasing demand for battery energy density in various fields, high-energy-density lithium-ion batteries are the focus of future research and development. The low specific capacity of traditional graphite-based negative electrode materials limits the improvement of lithium-ion battery energy density, while the theoretical lithium insertion capacity of silicon is about 10 times that of graphite, and it has the advantages of abundant reserves and no pollution, making it the most promising next-generation lithium-ion battery negative electrode material for commercial application. However, the volume expansion problem of silicon (≈300%), especially in dense silicon anodes, leads to structural pulverization and the continuous formation of unstable solid electrolyte membranes (SEI), which hinders the practical application of silicon-based anodes. In order to solve these problems, a lot of research has been done on the synthesis of silicon-based materials, including nanostructured silicon and silicon / carbon composites. Although silicon-based electrodes with high capacity and excellent electrochemical performance have begun to be used in some fields, the development of silicon-based anodes with high mass loading and high density remains a challenge.

[0003] Mesophase asphalt is a liquid crystal phase compound containing a considerable amount of mesophase, which is gradually formed when organic compounds such as petroleum residue, coal tar, and pure aromatic compounds are heat-treated at 350°C to 550°C due to a series of reactions such as continuous bond breaking, dehydrogenation, and polycondensation between molecules. It has a regularly oriented macromolecular sheet structure inside, is easily graphitized when treated at high temperature, and is a typical easy-to-graphitize carbon. As the most extensive source of negative electrode materials for lithium-ion batteries, asphalt-based carbon materials have the advantages of large output and mature industrialization. According to the definition, mesophase asphalt is an anisotropic substance in a large area generated by heavy aromatic hydrocarbons during heat treatment. Its structural morphology can usually be divided into mosaic type, streamlined type, wide-area type, etc. When observed under a polarizing microscope, its surface will show changes such as yellow, blue, and red, and the electrochemical properties of mesophase asphalts of different structures are also different. The present invention uses wide-area mesophase asphalt to further produce silicon-carbon composite materials, which can effectively realize the secondary utilization and product conversion of asphalt and enhance the added value of products. Summary of the invention

[0004] In order to overcome the shortcomings of the prior art, the present invention strictly controls the reaction conditions, uses a wide-area petroleum-based mesophase asphalt as the carbon source, and prepares a silicon-carbon composite material as the inner core through hydrothermal reaction and magnesium thermal reduction. Calcium carbonate is used as a sacrificial layer and the wide-area mesophase asphalt is used as a coating layer to successfully prepare a silicon-carbon composite electrode material with a quaternary structure of "carbon-silicon-void-carbon" with high specific capacity and high rate.

[0005] The object of the present invention is achieved through the following technical solutions:

[0006] A modification and preparation method of a wide-area mesophase pitch-based silicon-carbon composite electrode material comprises the following specific steps:

[0007] Step 1: Weigh a certain amount of wide-range mesophase pitch and perform ball milling at a mass ratio of 1:20. The ball milling medium is zirconium oxide balls. The ball-milled wide-range mesophase pitch is immersed in an organic strong alkali solution with a concentration of 5-10 mol / L. The mixture is vigorously stirred at 160°C-220°C for 4 hours to obtain a wide-range mesophase pitch activated by an alkali solution.

[0008] The organic strong base is one of potassium tert-butoxide, sodium tert-butoxide or tetramethylguanidine;

[0009] Step 2: The wide-area mesophase asphalt activated by the alkali solution is washed with deionized water until it is neutral and ultrasonically dispersed in a certain amount of deionized water / ethanol mixed solution, and the oxygen-containing organosilicon compound is added dropwise under ultrasound, and the solution after ultrasound is transferred to a hydrothermal reactor, and reacted at 160-200° C. for 6-15 hours; the hydrothermal reaction product is filtered, and the precipitate is washed three times with ethanol and deionized water respectively, and placed in an oven to dry to obtain a dry product;

[0010] The oxygen-containing organosilicon compound is selected from one of triisopropylsilyl trifluoromethanesulfonate, 3-tert-butyldimethylsilyl-2-propyn-1-ol or (1,1-dimethylethyl)dimethylsilyl trifluoromethanesulfonate;

[0011] Step 3: The dried product is mixed with Mg powder in a mass ratio of 10:1, reacted at 600°C in an argon / hydrogen mixed gas for 4-8 hours, and the obtained mixture is washed with dilute hydrochloric acid, ethanol and deionized water respectively until neutral to obtain a treated magnesium thermal reaction product;

[0012] Step 4: Ultrasonic dispersion of the treated magnesium thermal reaction product in deionized water, adding a certain amount of sodium carbonate and calcium chloride in turn, stirring vigorously to obtain a white precipitate uniformly coated with calcium carbonate; then adding the obtained white precipitate to a certain amount of a solution of a broad-domain mesophase asphalt, stirring for 24 hours, filtering, washing with deionized water and drying; placing the dried precipitate in a tubular furnace, pre-oxidizing at 300°C in an air atmosphere for 2-4 hours, and carbonizing at 800-1000°C in an argon atmosphere for 2 hours to obtain a carbonized product;

[0013] Step 5: Place the carbonization product in 0.1 mol / L hydrochloric acid, wash thoroughly to remove calcium carbonate precipitate, then wash with deionized water until neutral, and dry to obtain a wide-area mesophase asphalt-based silicon-carbon composite electrode material with a four-level core-shell structure of "carbon-silicon-void-carbon".

[0014] In the present invention, the silicon content of the product electrode material is controlled by the addition amount of the oxygen-containing organosilicon compound in the hydrothermal synthesis raw material. The more the oxygen-containing organosilicon compound is added, the higher the silicon content in the final product. However, too high a silicon content will cause a large volume expansion, causing the battery capacity to drop rapidly, while too low a silicon content will lead to insufficient specific capacity. Preferably, the ratio of the amount of the wide-area mesophase asphalt to the oxygen-containing organosilicon compound after ball milling is 1g:(0.2-0.6)g.

[0015] The mass of sodium carbonate and calcium chloride added in step 4 of the present invention and the mass of the magnesium thermal reaction product obtained in step 3 directly affect the cavity thickness of the composite electrode material, and then affect the tap density of the electrode material. Preferably, in step 4, the molar ratio of sodium carbonate to calcium chloride is controlled to be 1:1, and the mass ratio of the magnesium thermal reaction product to sodium carbonate is 2:1.

[0016] In step 4 of the present invention, the heating rate of the air atmosphere pre-oxidation process is 1°C / min.

[0017] The wide-range mesophase asphalt described in the present invention is a petroleum-based mesophase asphalt with anisotropic material size between 80 and 150 microns. The wide-range mesophase asphalt within this range has the highest specific capacity.

[0018] In the present invention, the method for preparing the solution of the broad-range mesophase asphalt is to dissolve the broad-range mesophase asphalt in a solvent, wherein the solvent is selected from one or more of tetrahydrofuran, toluene, N-methylpyrrolidone, and pyridine; the dosage ratio of the solvent to the broad-range mesophase asphalt is 200mL: (0.5-1.5)g.

[0019] In the present invention, in the "carbon-silicon-void-carbon" four-level core-shell wide-area mesophase asphalt-based silicon-carbon composite electrode material, the silicon layer thickness is 0.03-0.1 μm, the void structure thickness is 0.02-0.1 μm, and the outer carbon layer thickness is 0.02-0.1 μm.

[0020] The present invention also provides a wide-area mesophase asphalt-based silicon-carbon composite electrode material prepared by the above method, wherein the electrode material has a four-level core-shell structure of "carbon-silicon-void-carbon", a first-cycle coulomb efficiency of more than 70%, a reversible specific capacity of more than 550 mAh / g at a current density of 0.1C, and a specific capacity of more than 470 mAh / g at a high current density of 10C.

[0021] The classification of mesophase asphalt is determined based on the size of the monochromatic area presented by the anisotropic substances in the mesophase asphalt under orthogonal polarized light. Among them, the size distribution of anisotropic substances in the asphalt is above 60 microns, which is called wide-area mesophase asphalt. The anisotropic substances in the wide-area mesophase asphalt obtained by the present invention by controlling appropriate reaction conditions have a size between 80 and 150 microns, the arrangement orientation of the carbon layer building units inside the asphalt molecules is highly consistent, the flatness is large, and the consistency of the optical texture orientation is presented under a polarizing microscope. It has the characteristics of long-range crystal order, which ensures the stable insertion and extraction of lithium ions in the battery during long-term cycling. Compared with mesophase asphalts with other structures, it has better specific capacity and cycle stability. The present invention utilizes oxygen-containing organosilicon compounds as a silicon source, and through a hydrothermal reaction, the organosilicon is first deposited in situ on the surface of the carbon material to form a uniform coating layer, and the silicon-carbon bond is tighter; the void structure generated by calcium carbonate as a sacrificial layer reserves sufficient space for the expansion of silicon, and the outermost layer is again coated with wide-area asphalt to effectively restrain the excessive expansion of silicon. The prepared electrode material has the advantages of good conductivity, good rate performance, and stable cycle performance.

[0022] Compared with the prior art, the present invention has the following advantages:

[0023] 1. The wide-range mesophase asphalt prepared from heavy oil has the advantages of wide sources, low cost and high yield. The high flatness and consistent orientation of its internal carbon layer ensure the stable embedding and extraction of lithium ions during long-term cycling.

[0024] 2. After ball milling, the particle size of the broad-area mesophase asphalt is uniform and the tap density is high, which is beneficial to improving the specific capacity of the electrode material.

[0025] 3. The wide-area mesophase asphalt is first activated by an organic strong alkaline solution to enrich the functional groups on the surface of the material, which is beneficial to the subsequent in-situ composite of asphalt and silicon.

[0026] 4. Use organic silicon as the silicon source, and combine it with the functional groups on the surface of asphalt, so that the bond between silicon and the carbon substrate is tighter, which can effectively prevent the expansion and shedding of silicon during the electrode cycle.

[0027] 5. Calcium carbonate is used as a sacrificial layer to facilitate etching and reserve sufficient space for the volume expansion of the inner silicon layer; and the outermost coating carbon layer further restricts the expansion of silicon. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a polarized photo of the broad-spectrum mesophase pitch used in the present invention.

[0029] Figure 2 It is a schematic structural diagram of the wide-area mesophase asphalt-based silicon-carbon composite electrode material prepared by the present invention. DETAILED DESCRIPTION

[0030] In order to make the modification and preparation method of the wide-area mesophase asphalt-based silicon-carbon composite electrode material of the present invention more understandable, it is explained below with reference to examples.

[0031] Embodiment 1:

[0032] Step 1: Weigh a certain amount of broad-range mesophase pitch (anisotropic size of 80 to 150 microns) and mix it with 20g of zirconia balls, rotate at 800rpm, and ball-mill for 8h. Immerse 1g of the ball-milled broad-range mesophase pitch in 200ml of 5mol / L potassium tert-butoxide solution, and stir vigorously at 160°C for 4h to obtain a broad-range mesophase pitch activated by an alkaline solution;

[0033] Step 2: Wash the activated wide-area mesophase asphalt with deionized water until it is neutral and ultrasonically disperse it in 200 ml of a deionized water / ethanol mixed solution, the mass ratio of deionized water to ethanol is 1:1, and add 20 ml of a triisopropylsilyl trifluoromethanesulfonate ethanol solution with a mass concentration of 0.01 g / ml dropwise under ultrasound, and continue to ultrasonicate until it is completely dispersed; transfer the ultrasonicated solution to a hydrothermal reactor, react at 160°C for 8 hours, filter the hydrothermal reaction product, wash the precipitate with ethanol and deionized water three times respectively, and dry it in an oven at 80°C for 24 hours to obtain a dry product;

[0034] Step 3: 1.1 g of the dried product was mixed with 0.11 g of Mg powder, and reacted at 600° C. for 4 h in an argon / hydrogen mixture. The obtained mixture was washed with 0.1 mol / L dilute hydrochloric acid, ethanol and deionized water to neutrality, and dried to obtain a treated magnesium thermal reaction product;

[0035] Step 4: ultrasonically disperse 1 g of the treated magnesium thermal reaction product in deionized water, add 0.53 g of sodium carbonate and 0.55 g of calcium chloride in sequence, and stir vigorously to obtain a white precipitate uniformly coated with calcium carbonate; then add the obtained white precipitate to 200 ml of toluene solution of 0.5 g of wide-domain mesophase asphalt, stir for 24 h, filter, wash with deionized water and dry; place the dried precipitate in a tubular furnace, pre-oxidize at 300 ° C in air atmosphere for 2 h, and carbonize at 800 ° C in argon atmosphere for 2 h to obtain a carbonized product;

[0036] Step 5: Place the carbonized product in 0.1 mol / L hydrochloric acid, wash thoroughly to remove calcium carbonate precipitate, then wash with deionized water until neutral, and dry to obtain a wide-area intermediate phase asphalt-based silicon-carbon composite electrode material A, which has a four-level core-shell structure of "carbon-silicon-void-carbon", wherein the thickness of the silicon layer is 0.05 μm, the thickness of the void structure is 0.02 μm, and the thickness of the outer carbon layer is 0.05 μm.

[0037] Embodiment 2:

[0038] Step 1: Weigh a certain amount of broad-range mesophase pitch (anisotropic size of 80 to 150 microns) and mix it with 20g of zirconia balls, and ball-mill it at a speed of 800rpm for 8h. Immerse 1g of the ball-milled broad-range mesophase pitch in 200ml of 5mol / L potassium tert-butoxide solution, and vigorously stir it at 160°C for 4h to obtain the broad-range mesophase pitch activated by alkaline solution;

[0039] Step 2: The activated wide-area mesophase asphalt is washed with deionized water until it is neutral and ultrasonically dispersed in 200 ml of a deionized water / ethanol mixed solution, the mass ratio of deionized water to ethanol is 1:1, and 40 ml of a triisopropylsilyl trifluoromethanesulfonate ethanol solution with a mass concentration of 0.01 g / ml is added dropwise under ultrasound, and ultrasound is continued until it is completely dispersed; the ultrasonicated solution is transferred to a hydrothermal reactor, reacted at 160°C for 12 hours, the hydrothermal reaction product is filtered, and the precipitate is washed three times with ethanol and deionized water respectively, and placed in an oven at 80°C for 24 hours to obtain a dry product;

[0040] Step 3: 1.2 g of the dried product was mixed with 0.12 g of Mg powder, and reacted at 600° C. for 4 h in an argon / hydrogen mixture. The obtained mixture was washed with 0.1 mol / L dilute hydrochloric acid, ethanol and deionized water respectively until neutral, and dried to obtain a treated magnesium thermal reaction product;

[0041] Step 4: Ultrasonic dispersion of 1 g of the treated magnesium thermal reaction product in deionized water, and sequentially adding 0.53 g of sodium carbonate and 0.55 g of calcium chloride, stirring vigorously to obtain a white precipitate uniformly coated with calcium carbonate; then adding the obtained white precipitate to a 200 ml toluene solution of 0.5 g of a broad-domain mesophase asphalt, stirring for 24 h, filtering, washing with deionized water and drying; placing the dried precipitate in a tubular furnace, pre-oxidizing at 300° C. in an air atmosphere for 2 h, and carbonizing at 1000° C. in an argon atmosphere for 2 h to obtain a carbonized product;

[0042] Step 5: Place the carbonized product in 0.1 mol / L hydrochloric acid, wash thoroughly to remove calcium carbonate precipitate, then wash with deionized water until neutral, and dry to obtain a wide-area intermediate phase asphalt-based silicon-carbon composite electrode material B, which has a four-level core-shell structure of "carbon-silicon-void-carbon", wherein the thickness of the silicon layer is 0.08 μm, the thickness of the void structure is 0.02 μm, and the thickness of the outer carbon layer is 0.05 μm.

[0043] Embodiment 3:

[0044] Step 1: Weigh a certain amount of broad-range mesophase pitch (anisotropic size of 80 to 150 microns) and mix it with 20g of zirconia balls, and ball-mill it at a speed of 800rpm for 8h. Immerse 1g of the ball-milled broad-range mesophase pitch in 200ml of 5mol / L potassium tert-butoxide solution, and vigorously stir it at 160°C for 4h to obtain the broad-range mesophase pitch activated by alkaline solution;

[0045] Step 2: Wash the activated wide-area mesophase asphalt with deionized water until it is neutral and ultrasonically disperse it in 200 ml of a deionized water / ethanol mixed solution, the mass ratio of deionized water to ethanol is 1:1, and add 60 ml of a 0.01 g / ml triisopropylsilyl trifluoromethanesulfonate ethanol solution dropwise under ultrasound, and continue to ultrasonicate until it is completely dispersed; transfer the ultrasonicated solution to a hydrothermal reactor and react at 160°C for 12 hours; filter the hydrothermal reaction product, wash the precipitate with ethanol and deionized water three times respectively, and dry it in an oven at 80°C for 24 hours to obtain a dry product;

[0046] Step 3: 1.2 g of the dried product was mixed with 0.12 g of Mg powder, and reacted at 600° C. for 4 h in an argon / hydrogen mixture. The obtained mixture was washed with 0.1 mol / L dilute hydrochloric acid, ethanol and deionized water respectively until neutral, and dried to obtain a treated magnesium thermal reaction product;

[0047] Step 4: ultrasonically disperse 1 g of the treated magnesium thermal reaction product in deionized water, add 0.53 g of sodium carbonate and 0.55 g of calcium chloride in sequence, and stir vigorously to obtain a white precipitate uniformly coated with calcium carbonate; then add the obtained white precipitate to 200 ml of toluene solution of 0.5 g of wide-domain mesophase asphalt, stir for 24 h, filter, wash with deionized water and dry; place the dried precipitate in a tubular furnace, pre-oxidize at 300 ° C in air atmosphere for 2 h, and carbonize at 1100 ° C in argon atmosphere for 2 h to obtain a carbonized product;

[0048] Step 5: Place the carbonization product in 0.1 mol / L hydrochloric acid, wash thoroughly to remove calcium carbonate precipitate, then wash with deionized water until neutral, and dry to obtain a wide-area intermediate phase asphalt-based silicon-carbon composite electrode material C, which has a four-level core-shell structure of "carbon-silicon-void-carbon", wherein the thickness of the silicon layer is 0.08 μm, the thickness of the void structure is 0.03 μm, and the thickness of the outer carbon layer is 0.1 μm.

[0049] Embodiment 4:

[0050] Step 1: Weigh a certain amount of broad-range mesophase pitch (anisotropic size of 80 to 150 microns) and mix it with zirconium oxide balls, and ball-mill it at a speed of 800 rpm for 8 hours. Immerse 1g of the ball-milled broad-range mesophase pitch in 200ml of 7mol / L potassium tert-butoxide solution, and vigorously stir it at 160°C for 4 hours to obtain the broad-range mesophase pitch activated by alkaline solution;

[0051] Step 2: Wash the activated wide-area mesophase asphalt with deionized water until it is neutral and ultrasonically disperse it in 200 ml of a deionized water / ethanol mixed solution, the mass ratio of deionized water to ethanol is 1:1, and add 60 ml of 3-tert-butyldimethylsilyl-2-propyn-1-ol ethanol solution with a mass concentration of 0.01 g / ml dropwise under ultrasound, and continue to ultrasonicate until it is completely dispersed; transfer the ultrasonicated solution to a hydrothermal reactor and react at 160°C for 12 hours; filter the hydrothermal reaction product, wash the precipitate with ethanol and deionized water three times respectively, and dry it in an oven at 80°C for 24 hours to obtain a dry product;

[0052] Step 3: 1.2 g of the dried product was mixed with 0.12 g of Mg powder, and reacted at 600° C. for 4 h in an argon / hydrogen mixture. The obtained mixture was washed with 0.1 mol / L dilute hydrochloric acid, ethanol and deionized water respectively until neutral, and dried to obtain a treated magnesium thermal reaction product;

[0053] Step 4: Add 1 g of the treated magnesium thermal reaction product to 200 ml of toluene solution of 0.5 g of broad-area mesophase asphalt, stir for 24 hours, filter, wash with deionized water and dry; place the dried precipitate in a tubular furnace, pre-oxidize at 300°C in an air atmosphere for 2 hours, and carbonize at 1000°C in an argon atmosphere for 2 hours to obtain a broad-area mesophase asphalt-based silicon-carbon composite electrode material D, which has a three-level core-shell structure of "carbon-silicon-carbon", wherein the thickness of the silicon layer is 0.05 μm and the thickness of the outer carbon layer is 0.1 μm.

[0054] Embodiment 5:

[0055] This embodiment provides a modification preparation method of a petroleum coke-based silicon-carbon composite electrode material. The raw material petroleum coke used is Grade I petroleum coke that complies with GB / T 24533-2019, and its technical indicators are shown in Table 1.

[0056] Table 1 Main technical indicators of Grade I petroleum coke

[0057]

[0058] Step 1: Weigh a certain amount of petroleum coke and mix it with 20g of zirconium oxide balls, and ball-mill it at a speed of 800rpm for 8h. Immerse 1g of the ball-milled petroleum coke in 200ml of 7mol / L potassium tert-butoxide solution, and stir vigorously at 160℃ for 4h to obtain alkaline solution-activated petroleum coke;

[0059] Step 2: Wash the activated petroleum coke with deionized water until it is neutral and ultrasonically disperse it in 200 ml of a deionized water / ethanol mixed solution, the mass ratio of deionized water to ethanol is 1:1, and add 60 ml of 3-tert-butyldimethylsilyl-2-propyn-1-ol ethanol solution with a mass concentration of 0.01 g / ml dropwise under ultrasound, and continue to ultrasonicate until it is completely dispersed; transfer the ultrasonicated solution to a hydrothermal reactor and react at 160°C for 12 hours; filter the hydrothermal reaction product, wash the precipitate with ethanol and deionized water three times respectively, and dry it in an oven at 80°C for 24 hours to obtain a dry product;

[0060] Step 3: 1.2 g of the dried product was mixed with 0.12 g of Mg powder, and reacted at 600° C. for 4 h in an argon / hydrogen mixture; the obtained mixture was washed with 0.1 mol / L dilute hydrochloric acid, ethanol and deionized water respectively until neutral, and dried to obtain a treated magnesium thermal reaction product;

[0061] Step 4: Ultrasonic dispersion of 1 g of the treated magnesium thermal reaction product in deionized water, and sequentially adding 0.53 g of sodium carbonate and 0.55 g of calcium chloride, and vigorously stirring to obtain a white precipitate uniformly coated with calcium carbonate; then adding the obtained white precipitate to a 200 ml toluene solution of 0.5 g of petroleum coke, stirring for 24 h, filtering, washing with deionized water and drying; placing the dried precipitate in a tubular furnace, pre-oxidizing at 300° C. in an air atmosphere for 2 h, and carbonizing at 1000° C. in an argon atmosphere for 2 h to obtain a carbonized product;

[0062] Step 5: Place the carbonized product in 0.1 mol / L hydrochloric acid, wash thoroughly to remove calcium carbonate precipitate, then wash with deionized water until neutral, and dry to obtain a "carbon-silicon-void-carbon" four-level core-shell composite silicon-carbon electrode material E, wherein the silicon layer has a thickness of 0.05 μm, the void structure has a thickness of 0.04 μm, and the outer carbon layer has a thickness of 0.1 μm.

[0063] Embodiment 6:

[0064] Step 1: Weigh a certain amount of broad-range mesophase pitch (anisotropic size of 180 to 200 microns) and mix it with 20g of zirconia balls, and ball-mill it at a speed of 800rpm for 8h. Immerse 1g of the ball-milled broad-range mesophase pitch in 200ml of 5mol / L potassium tert-butoxide solution, and vigorously stir it at 160°C for 4h to obtain the broad-range mesophase pitch activated by alkaline solution;

[0065] Step 2: Wash the activated wide-area mesophase asphalt with deionized water until it is neutral and ultrasonically disperse it in 200 ml of a deionized water / ethanol mixed solution, the mass ratio of deionized water to ethanol is 1:1, and add 60 ml of a triisopropylsilyl trifluoromethanesulfonate ethanol solution with a mass concentration of 0.01 g / ml dropwise under ultrasound, and continue to ultrasonicate until it is completely dispersed; transfer the ultrasonicated solution to a hydrothermal reactor and react at 160°C for 12 hours; filter the hydrothermal reaction product, wash the precipitate with ethanol and deionized water three times respectively, and dry it in an oven at 80°C for 24 hours to obtain a dry product;

[0066] Step 3: 1.2 g of the dried product was mixed with 0.12 g of Mg powder, and reacted at 600° C. for 4 h in an argon / hydrogen mixture. The obtained mixture was washed with 0.1 mol / L dilute hydrochloric acid, ethanol and deionized water respectively until neutral, and dried to obtain a treated magnesium thermal reaction product;

[0067] Step 4: ultrasonically disperse 1 g of the treated magnesium thermal reaction product in deionized water, add 0.53 g of sodium carbonate and 0.55 g of calcium chloride in sequence, and stir vigorously to obtain a white precipitate uniformly coated with calcium carbonate; then add the obtained white precipitate to 200 ml of toluene solution of 0.5 g of wide-domain mesophase asphalt, stir for 24 h, filter, wash with deionized water and dry; place the dried precipitate in a tubular furnace, pre-oxidize at 300 ° C in air atmosphere for 2 h, and carbonize at 1100 ° C in argon atmosphere for 2 h to obtain a carbonized product;

[0068] Step 5: Place the carbonization product in 0.1 mol / L hydrochloric acid, wash thoroughly to remove calcium carbonate precipitate, then wash with deionized water until neutral, and dry to obtain a wide-area intermediate phase asphalt-based silicon-carbon composite electrode material C, which has a four-level core-shell structure of "carbon-silicon-void-carbon", wherein the thickness of the silicon layer is 0.08 μm, the thickness of the void structure is 0.03 μm, and the thickness of the outer carbon layer is 0.1 μm.

[0069] Battery performance test

[0070] 1. Electrode preparation: The electrode material AF obtained in Example 1-6 was mixed with acetylene black and PVDF in a mass ratio of 8:1:1, ground with NMP (nitromethylpyrrolidone) as solvent to form a uniform slurry and applied on a copper foil, vacuum dried at 90°C for 24h, and rolled to obtain an electrode sheet.

[0071] 2. Battery performance test: The obtained negative electrode sheet was cut into electrode sheets with a diameter of 12 mm for battery assembly. The assembly process was carried out in a glove box filled with Ar gas, and the water and oxygen content was less than 0.01 ppm. The battery used a CR2032 button cell, with a metal lithium sheet as the counter electrode, a polypropylene film as the diaphragm, and 1M lithium hexafluorophosphate (the solvent was a mixture of ethylene carbonate and dimethyl carbonate in a volume ratio of 1:1, with 5% fluoroethylene carbonate added) as the electrolyte. The assembled button cell was subjected to a 0.1C charge and discharge cycle performance test and a 5C rate performance test at 25°C and a voltage range of 0.05V-2.2V. The measured battery first cycle specific capacity (mAh / g), first charge and discharge efficiency (%), and reversible cycle specific capacity (mAh / g, 500 cycles) were recorded, and the silicon content in each electrode material was given. The results are shown in Table 2.

[0072] Table 2 Comparison of Si / C electrode material performance

[0073]

[0074] It can be seen from the data in Table 2 that the silicon-carbon composite electrode materials AC prepared by the method of the present invention have high reversible cycle specific capacity and first-cycle coulomb efficiency. By regulating the mass of the oxygen-containing organosilicon compound added during the hydrothermal process, the silicon content in the final product can be effectively regulated, and as the silicon content in the composite material increases, the reversible cycle specific capacity of the material gradually increases. Considering the various properties of the prepared electrode material, a silicon loading of about 7% can bring the best electrochemical performance. Compared with electrode material D, electrode material C uses the same type of asphalt, but no void structure is introduced into electrode material D. It can be clearly seen from the table that the reversible cycle specific capacity of electrode material D is lower than that of electrode material AC, which illustrates the excellence of the four-level "carbon-silicon-void-carbon" structure synthesized by the present invention. Compared with electrode material E, electrode material C has the same structure but uses different types of asphalt. In material C, broad-area mesophase asphalt is preferably used as the carbon source, and material E uses grade I petroleum coke that complies with GB / T 24533-2019. It can be seen that the specific capacities of electrode materials C and E are basically the same after 100 cycles. However, when the cycle reaches 500 cycles, the specific capacities of the two are quite different, which are 90.54% and 82.63% of the specific capacities at 100 cycles, respectively. The reversible cycle specific capacities of electrode materials A and B at 500 cycles are 91.4% and 89.6% of those at 100 cycles, respectively. This indicates that the broad-area mesophase asphalt used in the present invention has significantly excellent stability in long cycles. Compared with electrode material AC, electrode material F has the same structure, but the anisotropic size of the broad-area mesophase asphalt used in electrode material F is 180-200 microns, and the first-cycle coulombic efficiency and the reversible cycle specific capacity at 500 cycles are lower than those of electrode material AF, indicating that the broad-area mesophase asphalt with an anisotropic size in the range of 80-150 microns used in the present invention has the highest specific capacity and first-cycle coulombic efficiency.

Claims

1. A modification and preparation method of a wide-area mesophase pitch-based silicon-carbon composite electrode material, characterized in that: The specific steps include: Step 1: Weigh a certain amount of wide-area mesophase pitch and mix it with 20g of ball milling medium for ball milling treatment, the ball milling medium is zirconium oxide ball, immerse 1g of the ball-milled wide-area mesophase pitch in a 5-10mol / L organic strong alkali solution, and vigorously stir it at 160℃-220℃ for 4h to obtain the wide-area mesophase pitch activated by the alkali solution; Step 2: The wide-area mesophase asphalt activated by the alkali solution is washed with deionized water until it is neutral and ultrasonically dispersed in a certain amount of deionized water / ethanol mixed solution, and the oxygen-containing organosilicon compound is added dropwise under ultrasound, and the solution after ultrasound is transferred to a hydrothermal reactor, and reacted at 160-200° C. for 6-15 hours; the hydrothermal reaction product is filtered, and the precipitate is washed three times with ethanol and deionized water respectively, and placed in an oven to dry to obtain a dry product; Step 3: The dried product is mixed with Mg powder in a mass ratio of 10:1, reacted at 600°C in an argon / hydrogen mixed gas for 4-8 hours, and the obtained mixture is washed with dilute hydrochloric acid, ethanol and deionized water respectively until neutral to obtain a treated magnesium thermal reaction product; Step 4: Ultrasonic dispersion of the treated magnesium thermal reaction product in deionized water, adding a certain amount of sodium carbonate and calcium chloride in turn, stirring vigorously to obtain a white precipitate uniformly coated with calcium carbonate; then adding the obtained white precipitate to a certain amount of a solution of a broad-domain mesophase asphalt, stirring for 24 hours, filtering, washing with deionized water and drying; placing the dried precipitate in a tubular furnace, pre-oxidizing at 300°C in an air atmosphere for 2-4 hours, and carbonizing at 800-1000°C in an argon atmosphere for 2 hours to obtain a carbonized product; Step 5: Place the carbonized product in 0.1 mol / L hydrochloric acid, wash thoroughly to remove calcium carbonate precipitate, then wash with deionized water until neutral, and dry to obtain a wide-area mesophase asphalt-based silicon-carbon composite electrode material with a four-level core-shell structure of "carbon-silicon-void-carbon".

2. The modification preparation method of a wide-area mesophase pitch-based silicon-carbon composite electrode material according to claim 1, characterized in that: The wide-area mesophase asphalt is a petroleum-based mesophase asphalt with an anisotropic material size between 80 and 150 microns, and exhibits consistency in optical texture orientation under a polarizing microscope.

3. The modification preparation method of a wide-area mesophase pitch-based silicon-carbon composite electrode material according to claim 1, characterized in that: The organic strong base is one of potassium tert-butoxide, sodium tert-butoxide or tetramethylguanidine; The oxygen-containing organic silicon compound is selected from one of triisopropylsilyl trifluoromethanesulfonate, 3-tert-butyldimethylsilyl-2-propyn-1-ol or (1,1-dimethylethyl)dimethylsilyl trifluoromethanesulfonate.

4. The modification and preparation method of a wide-area mesophase pitch-based silicon-carbon composite electrode material according to claim 1, characterized in that: The dosage ratio of the ball-milled broad-domain mesophase asphalt to the oxygen-containing organosilicon compound is 1g:(0.2-0.6)g.

5. The modification and preparation method of a wide-area mesophase pitch-based silicon-carbon composite electrode material according to claim 1, characterized in that; In step 4, the molar ratio of sodium carbonate to calcium chloride is controlled to be 1:1, and the mass ratio of the magnesium thermal reaction product to sodium carbonate is controlled to be 2:

1.

6. The modification and preparation method of a wide-area mesophase pitch-based silicon-carbon composite electrode material according to claim 1, characterized in that; The heating rate of the air atmosphere pre-oxidation process is 1℃ / min.

7. The modification and preparation method of a wide-area mesophase pitch-based silicon-carbon composite electrode material according to claim 1, characterized in that: The method for preparing a solution of the broad-range mesophase asphalt is to dissolve the broad-range mesophase asphalt in a solvent, wherein the solvent is selected from one or more of tetrahydrofuran, toluene, N-methylpyrrolidone, and pyridine; the ratio of the solvent to the broad-range mesophase asphalt is 200 mL: (0.5-1.5) g.

8. The modification preparation method of a wide-area mesophase pitch-based silicon-carbon composite electrode material according to claim 1, characterized in that: In the electrode material, the thickness of the silicon layer is 0.03-0.1 μm, the thickness of the void structure is 0.02-0.1 μm, and the thickness of the outer carbon layer is 0.02-0.1 μm.

9. A wide-area mesophase pitch-based silicon-carbon composite electrode material, characterized in that: The electrode material is prepared by the modification preparation method described in any one of claims 1 to 8, and has a first-cycle coulombic efficiency of more than 70%, a reversible specific capacity of more than 550 mAh / g at a current density of 0.1C, and a specific capacity of more than 470 mAh / g at a high current density of 10C.

Citation Information

Patent Citations

  • Method for preparing needle coke

    CN104673341A

  • Processes for producing coke, artificial graphite and carbon material for negative electrode of non-aqueous solvent type secondary battery and pitch composition used therefor

    US20020027066A1